Narcolepsy and ROHHAD Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Ghent University Hospital, Belgium; Radboud University Nijmegen Medical Centre, and Sleep Medicine Centre, Heeze, Netherlands, report a 7-year-old girl with rapid-onset obesity, hypothalamic dysfunction, hypoventilation, and autonomic dysregulation (ROHHAD syndrome).